Eco-friendly utilization of microplastics for preparing coal water slurry: rheological behavior and dispersion mechanism. (1st January 2022) - Jiang, Xiaofeng; Chen, Shixing; Cui, Lifeng; Xu, Enle; Chen, Hongji; Meng, Xianliang; Wu, Guoguang
Abstract: Microplastics (MPs) are emergingly hazardous contaminants which ubiquitously exists in aquatic, terrestrial and atmospheric system, as well as in human system. Coal water slurry (CWS) is an important clean-coal-based liquid fuel with the characteristics of high-efficiency and low-pollution. This paper aims to implement the principles of clean production and prepare CWS by coblending coal particles and polyethylene terephthalate (PET) microplastics. It shows that the presence of PET particles significantly reduces the viscosity and increases the dispersion performance of CWS suspension. The apparent viscosity of CWS tends to decrease with the increase of PET content. Through the contact angle, surface morphology, and zeta potential analyses, particles with stronger hydrophobicity, more spherical shape and higher electronegativity, are more easily to form consistent and dispersed CWS suspensions. The extended DLVO theory demonstrates that the repulsion between solid particles becomes larger when PET particles are added to the slurry, which is beneficial to particle dispersion. In addition, the dispersant interfacial distribution differs between coal and PET particles, and significantly affect the rheological behavior and dispersion mechanism of CWS. This study proposes a potential approach to recycle the hazardous waste MPs and provides theoretical basis for enhancing CWS dispersion performance through coblending with PET microplastic particles. Highlights: CWS suspension exhibits shearing-thinning behavior. The apparent viscosity of CWS decreases with the increase of PET content. The addition of PET particles facilitates the CWS consistency and dispersion. The inter-particle repulsion becomes stronger in presence of PET.